Kajian Yuridis Waralaba Dalam Persfektif Hak Kekayaan Intelektual - I Kadek Agus Arnawa Pariwesa Putra; I Nyoman Putu Budiartha; Ni Made Puspasutari Ujianti (Fakultas Hukum Universitas Warmadewa, 2022)
Along with the development of the era of globalization, it also has an impact on the development of business concepts. One of them is the franchise system, which has recently become the center of attention as a form of business development breakthrough. The formulation of the problem is: how is the validity and legal force of the franchise agreement? And how are the legal consequences of franchise agreements related to IPR? The type of research is normative legal research and a statutory and conceptual approach to problems. The validity and legal force of the franchise agreement where the Civil Code adheres to the principle of consensualism, meaning that an agreement must be considered born at the time of reaching an agreement between the two parties. The franchise agreement begins to bind the parties and acts as law for those who make it, starting from the date the parties' agreement is reached and the agreement they make has the same legal force. The legal consequence of a franchise agreement related to IPR is the signing of a franchise agreement that has regulated IPR in it, the franchisor is obliged to give exclusive rights to the franchisee, and the franchisee can use the name and management system of the franchisor in a location, for an agreed period of time. The franchisor is obliged to maintain the benefits of the intellectual property rights and pay fees to the franchisor for the benefits of the intellectual property rights used. In the event that one of the parties in the agreement does not implement it, the other party in the agreement has the right to impose its implementation through the applicable legal mechanisms and channels. And if the consumer is not satisfied with the results, they can file a complaint with the franchisor.